Performance comparison of zero-Schottky-barrier and doped contacts carbon nanotube transistors with strain applied - Wahab, Md. Abdul; Alam, Khairul (Nano-Micro Letters, 2010)
Atomistic quantum simulation is performed to compare the performance of zero-Schottky-barrier and doped source-drain contacts carbon nanotube field effect transistors (CNTFETs) with strain applied. The doped source-drain contact CNTFETs outperform the Schottky contact devices with and without strain applied. The off-state current in both types of contact is similar with and without strain applied. This is because both types of contact offer very similar potential barrier in off-state. However, the on-state current in doped contact devices is much higher due to better modulation of on-state potential profile, and its variation with strain is sensitive to the device contact type. The on/off current ratio and the inverse subthreshold slope are better with doped source-drain contact, and their variations with strain are relatively less sensitive to the device contact type. The channel transconductance and device switching performance are much better with doped source-drain contact, and their variations with strain are sensitive to device contact type.